Financial Planning Linen Rental Laundry with RFID Technology in PT. Think Clean Laundry - Zamzami, Muhammad; Indradewa, Rhian; Nugroho, Sukmo Hadi; Iskandar, Muhammad Dhafi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research uses qualitative methods. Qualitative methods are scientific approaches aimed at understanding the meaning, interpretation, and context of the phenomena being studied. This approach emphasizes in-depth descriptions, understanding, and analysis that focus on qualitative rather than quantitative aspects. The capital planning of PT. Think Clean Laundry is sourced from 70% company founders, 20% from investors, and 10% from bank loans. Revenue planning for the first year is set at IDR 3,987,000,000, with the Break-Even Point achieved in the first year and the Payback Period in 2 years and 5 months. The result of NPV > 0 indicates that the investment made provides benefits to the company, allowing the project to be carried out. According to the five-year ROI calculation at PT. Think Clean Laundry, the effectiveness of the investment in generating profits relative to the costs incurred was realized in the first year. This indicates that PT. Think Clean Laundry achieved significant profits and is able to continue its investment in the following years. Financial planning to ensure the success of the Linen Rental Laundry business using RFID technology at PT. Think Clean Laundry plays a crucial role in managing the company's financial statements.